Report on professional attachment with Hoon Tai Meng & CO. - Lee, Foong Yee. (2008)
The report provide a summary of the attachment, highlighting several assignments that I received and found most stimulating, review the benefits received in terms of both auditing techniques and social skills, and provide suggestions.